Innovating Democracy Against Democratic Stress in Europe: Social Movements and Democratic Experiments - della Porta, Donatella; Felicetti, Andrea (Representation, 2019)
We investigate the interaction between democratic innovations and social movements in the context of the growing stress on representative democracy in Europe. In particular, we focus on citizen-led democratic innovations that emerged from popular protests against national political systems. We explore the crowd-sourced Constitutional Reform in Iceland and the G1000 in Belgium and consider three different stages: the onset of these innovations, their execution and their consequences. These innovations respond to a need for radical democratic reform. The extent to which the state might (or might not) be involved is a matter of paramount importance in the implementation of these experiments. Collaborating with institutions might provide valuable resources. At the same time it might marginalise the role and demands of civil society actors that instigated the processes in the first place. Rather than aiming at policy change only, citizen-led innovations might be in a good position to impact public spheres and to inspire similar initiatives in different contexts. We call for greater attention to the role of mobilisation in democratic innovation processes. This is particularly necessary at a time when democratic experiments grow in importance within social movements and in mainstream politics.